Peran Teknologi Terhadap Lingkungan Bisnis Internasional - Novy Arisca; Hendra Ibrahim (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to explore and analyze the implementation of the role of the technological environment on the dynamics of the international business environment. We use the literature study method to collect and analyze the latest information about how technological advances influence business strategies and company interactions in the global market. It is hoped that the results of this research will provide in-depth insight into the role of technology in the context of the international business environment